Prevalence of dental trauma in 5-6, 12 and 15-year-old children in Iran - Al-Shuhayeb, Muna; Ghaznavi, Dara; Parandeh Shirvan, Hoda; Ghasemianpour, M; Khoshnevisan, MH (Journal of Contemporary Medical Sciences, 2019)
Abstract Objectives: This study assessed the prevalence of dental trauma among the 5-6, 12 and 15-year-old Iranian children. Age, sex and place of residence of children with dental trauma and the correlation between parental level of education and prevalence of dental trauma were also evaluated. Methods: In this descriptive, cross-sectional study, we used the 2012-national survey data on oral health, which included a sample of Iranian individuals recruited from all provinces of Iran. A cluster random sample of 26,000 children in 3 age groups were included in this study. SPSS software was used for statistical analysis after quality control and data clean up. Results: The overall prevalence of dental trauma was 4.1% for the total sample. This value was 5.4% in boys and 3.1% in girls. The most common age of occurrence was 15 years (6%) followed by 12 years (4.9%) and 5-6 years (1.5%) of age. The highest percentage of dental trauma in 12 and 15-year-old children was noted in â€œKohkiloye and Boyerahmadâ€ Province. Higher level of parental education was associated with lower frequency of trauma in all age groups. The prevalence of dental trauma was lower among those residing in rural compared with urban areas. Conclusion: This study demonstrated relatively high prevalence of dental traumatic injuries among 5-15 year-old Iranian children (4.1%). Based on the reported associations, more effort is necessary to educate all parents and children on trauma prevention with priority in urban areas.